Belief in God among South African youth and its relation to their religious socialization and praxis - Ven, Jobannes A. P. van der (Hervormde teologiese studies, 1997)
This article investigates belief in God among 538 students from standard 9 who attend Anglican and Catholic schools in the Johannesburg/Pretoria region, and relates this belief to the students' religious socialization and praxis. The students' belief in God appears to correlate strongly with their religious praxis in the present and less so with their religious socialization. However, some elements within this religious socialization play a rather important role, namely the parents' religious modeling, communication, and transfer. Two elements do not appear to have any influence at all, namely the parents' church participation and the parents' religious steering of students in the past and present.